2012
DOI: 10.1007/s13758-012-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Permeability and in Mechanical Properties of Layer-by-Layer Films Made from Poly(allylamine) and Montmorillonite Postmodified upon Reaction with Dopamine

Abstract: Polyelectrolyte multilayer (PEM) films present a versatile surface functionalization method allowing to address many applications. These coatings suffer; however, from weak mechanical properties this problem can be addressed by the regular incorporation of clays in the layering process. To allow for an even better control of a whole set of film properties, among them their thermal stability, their stability in water, and their impermeability to anions, we postmodify (PAH-MMT)n films with polydopamine, by putti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…They found that, by deposition of different number of polyelectrolyte layers on an electrode it is possible to tune blocking degree of the electrode surface [45]. Similar studies of the permeability and mechanical properties of multilayers composed from polyelectrolytes and montmorillonite clay were investigated by Ball et al [46] and Elzbieciak et al [47]. The differences in permeability of linearly and exponentially growing polyelectrolyte films were discussed by Michel et al [48], but without quantifying them.…”
Section: Introductionmentioning
confidence: 92%
“…They found that, by deposition of different number of polyelectrolyte layers on an electrode it is possible to tune blocking degree of the electrode surface [45]. Similar studies of the permeability and mechanical properties of multilayers composed from polyelectrolytes and montmorillonite clay were investigated by Ball et al [46] and Elzbieciak et al [47]. The differences in permeability of linearly and exponentially growing polyelectrolyte films were discussed by Michel et al [48], but without quantifying them.…”
Section: Introductionmentioning
confidence: 92%
“…The diffusion path can be altered through precise tailoring of the thin lm architecture (i.e., polymer mortar composition/thickness and clay spacing/packing/aspect ratio). 10,13,14 Aside from their obvious promise for packaging applications, these polymer/silicate LbL multilayers are also being investigated for their mechanical properties [15][16][17][18] and a variety of end-use applications such as diffusion barriers, 19,20 sensors, 21,22 drug delivery, [23][24][25] and re protection. [26][27][28][29] Rigid polyurethane (PU), which is widely used in the building industry due to its heat insulating properties, and exible polyurethane, commonly used in upholstered furniture, are highly ammable materials susceptible to fast ame-spread and high heat release.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy to incorporate PDA in films deposited according to the layer-by-layer deposition method is to use those films as templates for the formation of PDA from dopamine solutions in the presence of O 2 as an oxidant [42,43].…”
Section: Composites Of Polydopamine With Organic Materialsmentioning
confidence: 99%
“…The same concept has been adapted for films made from the alternate adsorption of poly(allylamine) and clay platelets (montmorillonite, MMT). The obtained composite films kept the layered structure of the original (PAH–MMT) n films (Figure 3a,b), became impermeable to hexacyanoferrate anions (Figure 3c), smoother and more homogeneous in their elasticity even if the average Young’s modulus (1 GPa) decreased with respect to the unmodified multilayered film (4.5 GPa) (Figure 3d) [43].…”
Section: Composites Of Polydopamine With Organic Materialsmentioning
confidence: 99%
See 1 more Smart Citation